Thermal Modelling and Energy Management of a Smart Home with Renewable Energy Sources - Ozel, Onur; Boynuegri, Ali Rifat (IEEE, 2020)
In this paper, A monthly energy consumption calculation method according to the TS 825 standard is explained in detail to calculate the thermal heat loss in a smart building consist of ten apartments. Also, this method modified to a dynamic model for thermal heat loss calculations of the system and it is verified in simulations. Within the scope of energy management, energy requirement for an enough comfort level is calculated. In the smart residential building model, an energy production system consisting of wind energy and solar energy will be used. The relationship between the energy consumption requirement and the amount of production will be examined. In this smart home system, energy management will be carried out by performing operations such as energy thermal storage which is called power to heat (P2H) and load shifting. For this purpose, a dynamic thermal model of a smart residential building is realized.
Keywords: Smart home; energy management; thermal model; renewable energy; power to heat; BUILDING ENVELOPE; FORM; Energy & Fuels; Engineering